2019
DOI: 10.1109/access.2019.2916952
|View full text |Cite
|
Sign up to set email alerts
|

Impact Factor Identification for Switching Overvoltage in an Offshore Wind Farm by Analyzing Multiple Ignition Transients

Abstract: This paper investigates the impact factors of switching transient overvoltage (SOV) in an offshore wind farm (OWF) by analyzing multiple ignitions of a vacuum circuit breaker. The statistical features of transient overvoltages, which occur under real switching operation scenarios, are analyzed based on the measurements in a laboratory platform that is built according to the configuration of an actual OWF. Next, an OWF simulation transient model is established considering high-frequency characteristics of circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For each topology, different mitigation techniques were applied individually one by one to assess their capability in reducing the switching overvoltages. The mitigation techniques studied include four schemes that showed their effectiveness in literature namely; RC snubber circuit 8 , 9 , 11 , Pre-Insertion Resistor (PIR) 12 and surge capacitor 33 . The value of the parameters of each scheme (R and/or C) were set to reach maximum reduction in overvoltages based on defined ranges from literature 34 .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…For each topology, different mitigation techniques were applied individually one by one to assess their capability in reducing the switching overvoltages. The mitigation techniques studied include four schemes that showed their effectiveness in literature namely; RC snubber circuit 8 , 9 , 11 , Pre-Insertion Resistor (PIR) 12 and surge capacitor 33 . The value of the parameters of each scheme (R and/or C) were set to reach maximum reduction in overvoltages based on defined ranges from literature 34 .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Vacuum circuit breakers (VCBs) are widely used in switching wind farms because of their advantages of having lower maintenance requirements and longer operation life [11], [12], [13], [15], [17], [18], [24], [25], [26], [27], [28], [29], [32]. The VCB was modeled on ATP as a switch which was controlled using the MODELS component.…”
Section: Modeling Of the System A Modeling Of The Vacuum Circuit Breakermentioning
confidence: 99%
“…Also, the HF current may couple to the other phases, producing current zeros. Thus virtual chopping occurs, causing overvoltage in other phases [10,21]. In the process of multiple reignitions, the interval between the two reignitions is extremely short.…”
Section: Vcb Modelmentioning
confidence: 99%
“…In 2004, at Horns Rev, the largest OWF in Denmark at that time, almost all the tower terminal transformers suffered insulation fault accidents [9]. In [10], the authors reported an accident of transformer insulation damage occurred by switching off a vacuum circuit breaker (VCB) after connecting with the shunt reactor in Wailuo OWF. Studies have shown that the high-frequency (HF) overvoltage generated by the frequent switching on and off for VCBs was the main factor causing insulation fault of the transformers [11][12][13].…”
Section: Introductionmentioning
confidence: 99%